Possible EU futures for CRISPR-edited plants: Little margin for optimism? - Escajedo San-Epifanio, Leire; Filibi, Igor; Lasa López, Ainhoa; Puigdomènech, Pere; Uncetabarrenechea Larrabe, Javier (Frontiers in Plant Science, 2023)
This research article addresses the scenarios that may be encountered by the first application for pre-market approval of a CRISPR-edited plant in the EU. Two alternative scenarios are considered in the short and medium term. One of these possible EU futures depends on the final drafting and approval of EU legislation on certain New Genomic Techniques, which was started in 2021 and is due to be finalised before the next European Parliament elections in 2024. Since the proposed legislation excludes plants with foreign DNA, two different approval processes for CRISPR-edited plants will coexist if the legislation enters into force: one for plants whose genome has been altered, resulting in mutagenesis, cisgenesis and intragenesis; and the second for plants whose alterations result in transgenesis in general. In the event that this legislative process does not succeed, CRISPR-edited plants in the EU could face a regulatory scenario whose foundations were laid in the 1990s: the regulatory framework that applies to GM crops, food and feed. In this review, an ad hoc analytical framework has been built that considers in depth the two possible futures for CRISPR-edited plants in the EU. This framework emphasises the way in which the European Union and the Member States (MS), with their respective national interests, have historically shaped the regulatory framework for plant breeding in the EU. On the basis of the analyses carried out on the two possible futures for CRISPR-edited plants and of their potential with respect to plant breeding, the main conclusions are the following. Firstly, that the regulatory review that started in 2021 is not in itself "good enough" for plant breeding and CRISPR-edited plants. Secondly, that compared to its alternative, the regulatory review currently underway contains at least some promising improvements in the short term. Hence, thirdly, in addition to adopting the current regulation, the MS need to continue to work towards a substantial improvement in the legal status of plant breeding in the EU in the medium term.